Metolachlor Exposure Impaired Neurogenesis During Embryonic Development of Zebrafish (Danio rerio) - Martina Fazzina; Stefano Insidioso; Pietro Cacialli (Fishes, 2025)
The presence of pesticides in surface waters has been widely reported worldwide and represents a significant problem that raises concerns on local, regional, national, and international scales. Among these, metolachlor is one of the most widely used herbicides to control annual grasses and broadleaf weeds in various crops. Despite the existing research, data on the effects of metolachlor on the nervous system of fishes, remain limited. The present study aims to investigate the impact of metolachlor during embryonic development on the formation of the nervous system and the subsequent inflammatory response in zebrafish (Danio rerio), focusing specifically on larvae at 24 h post-fertilization (hpf). To achieve this, transgenic zebrafish lines marking neuronal populations Tg(Hu:GFP), glial cells Tg(gfap:GFP), and circulating macrophages Tg(mpeg:GFP) were employed. Following exposure to sub-lethal doses of metolachlor, we observed a significant decrease in GPF-positive cells marking the neuronal population, accompanied by an increase in apoptotic cells within the brain region. Additionally, treated embryos exhibited a marked neuroinflammatory response, characterized by astrogliosis and the specific accumulation of microglia/macrophage-positive cells in the head region. In situ hybridization and real-time PCR analyses revealed a significant downregulation of the neurogenin-1 (ngn1) transcript and a noticeable upregulation of the pro-inflammatory cytokine interleukin-1 beta (il1b). Our findings contribute to the growing body of evidence suggesting that metolachlor, even at early developmental stages, can have detrimental effects on both the formation of the nervous system and the regulation of immune responses.